Inclusive learning model in equivalency education Package A equivalent to elementary school: a case study at UPTD SKB Magetan - Ardy, Pregananda Aquar; Budiarti, Melik (At- Ta'lim : Jurnal Pendidikan, 2025)
This study aims to explore the implementation of inclusive teaching models within the context of equivalency education, specifically the Paket A program, which is equivalent to elementary education, at UPTD SKB Magetan. Equivalency education and inclusive education in Indonesia play a crucial role in providing equal opportunities for all individuals, including those with special needs, to access quality education. The differentiated learning model was identified as a relevant approach to meet the diverse learning needs of students, especially in inclusive classrooms. This research employs a qualitative method with a case study design, involving interviews and observations of teachers instructing students with special needs at UPTD SKB Magetan. The results show that the differentiated learning model is implemented by adapting content, processes, and assessments according to students' abilities, interests, and learning styles. Challenges faced in the implementation of this model include time constraints, limited resources, and the need for teacher training. Despite these challenges, the benefits are significant, including increased student engagement, motivation, and achievement for students with special needs. The study concludes that the differentiated learning model is an effective approach in inclusive education, helping to create a more inclusive learning environment that supports the success of all students, including those with special needs.